RASIO KEUANGAN UNTUK MENGETAHUI KINERJA PEMERINTAHAN - Kondjol, Ester Hesty (LPPM Politeknik Saint Paul Sorong, 2021)
Local government financial ratios show a good financial position or canbe seen from the performance of their government and government financial ratios consist of efficiency ratios, PAD effectiveness ratios, compatibility ratios, growth ratios, financial independence ratios. This type of research aims to analyze financial ratios.